Stable MgO nanoparticles for catalytic and pharmaceutical applications / Mohd Sufri Mastuli ... [et al.] - Mastuli, Mohd Sufri; Kamarulzaman, Che Norlida; Mahat, Annie Maria; Elong, Kelimah; Rusdi, Roshidah (Research Innovation Business Unit, 2014)
Magnesium oxide (MgO) is a versatile metal oxide having numerous applications in many fields. It has been used as a catalyst and catalyst support for various organic reactions, as an adsorbent for removing dyes and heavy metals from wastewater, as an antimicrobial material, as an electrochemical biosensor and many other applications. Some properties of MgO, such as catalytic behaviour, can be further improved if it is used as nano sized particles compared to micron-sized particles. Therefore, the formation of MgO nanostructures with a small crystallite size of less than 100 nm and homogenous morphology has attracted much attention due to their unique physicochemical properties including high surface area-to-volume ratio. It is widely accepted that the properties of the MgO nanostructures depend strongly on the synthesis methods and the processing conditions. Much effort has been devoted to synthesize MgO nanostructures using various methods such as precipitation, solvothermal, chemical vapour deposition, and electrochemical, sonochemical, microwave, electron spinning, and combustion, template and carbothermic reduction. Each method has its own advantages and disadvantages. An important issue regarding synthesis and preparation of nanostructured MgO is controlling the parameters in order to obtain a more uniform size as well as morphology of the nanoparticles. A sol-gel method is a promising technique for the formation of magnesium oxalic dehydrates followed by annealing at a suitable temperature to form MgO. The advantages are its simplicity, cost-effectiveness, low reaction temperature, high surface area-to-volume ratio, narrow particle size distribution and high purity of the final product. In the preparation of the nanostructured materials, it is important to optimize synthesis parameters in order to obtain the desired materials. To the best of our knowledge, there is no report on the effect of the molecular structure of complexing agents on MgO nanostructures even though the controlled of the nanostructures presents an important part of nanotechnology work. This work investigates the role of complexing agents, oxalic acid and tartaric acid, in the production of MgO nanocrystals. Results from simultaneous gravimetric analysis (STA) show that the two different synthesis routes yield precursors with different thermal profiles. It is found that thermal profiles of the precursors can reveal the effects of crystal growth during thermal annealing. X-Ray diffraction confirms that the final products are pure, single phase and of cubic shape. It is also found that complexing agents can affect the rate of crystal growth. The structures of the oxalic and tartaric acid as well as the complexation sites play very important roles in the formation of the nanocrystals. The complexing agents influence the rate of growth which affects the final crystallite size of the materials. Surprisingly, it is also found that oxalic acid and tartaric acid act as surfactant inhibiting crystal growth even at a high temperature of 950 degree Celsius and a long annealing time of 36 h. The crystallite formation routes are proposed to be via linear and branched polymer networks due to the different structures of the complexing agents. The catalytic properties of the MgO dependent on the particle size of MgO nanomaterials. The use of oxalic and tartaric acid has been demonstrated to be very useful in producing thermally stable MgO nanostructures with a relatively uniform particle size.